Indirect Effects of COVID-19 Nonpharmaceutical Interventions on Vaccine Acceptance - Bussolo, Maurizio; Sarma, Nayantara; Torre, Iván (Washington, DC : World Bank, 2022)
The information set from which individuals make their decision on vaccination includes signals from trusted agents, such as governments, community leaders, and the media. By implementing restrictions, or by relaxing them, governments can provide a signal about the underlying risk of the pandemic and indirectly affect vaccination take-up. Rather than focusing on measures specifically designed to increase vaccine acceptance, this paper studies how governments’ nonpharmaceutical policy responses to the pandemic can modify the degree of preventive health behavior, including vaccination. To do so, the paper uses repeated waves of a global survey on COVID-19 beliefs, behaviors, and norms covering 67 countries from August 2020 to February 2021. Controlling for the usual determinants, the analysis explores how individuals’ willingness to get vaccinated is affected by changes in government restriction measures (as measured by the Oxford Stringency Index). This relationship is mediated by individual characteristics, social norms (social pressure to conform with what most people do), and trust in government institutions. The results point to a complex picture as the implementation of restrictions is associated with increased acceptance in some contexts and decreased acceptance in others. The stringency of government restrictions has significant positive correlations with vaccine acceptance in contexts of weak social norms of vaccine acceptance and lower trust in government. In countries or communities where social norms are tighter and trust in government health authorities is high, vaccine acceptance is high but less sensitive to changes in policies. These results suggest that the indirect effect of government policy stringency is stronger among individuals who report lower trust and weaker social norms of vaccine acceptance.